Pengaruh Debt To Asset Ratio dan Debt To Equity Ratio terhadap Kinerja Keuangan pada Perusahaan Otomotif yang Terdaftar di BEI Periode 2015-2018 - Dian Permata Sari; Wan Suryani; Hesti Sabrina (Jurnal Ilmiah Manajemen dan Bisnis (JIMBI), 2021)
The purpose of this study is to find out the effect of debt to asset ratio (DAR) on the financial performance of the company, to know the effect of debt to equity ratio (DER) on the financial performance of the company and to know the effect of debt to asset ratio (DAR) and debt to equity ratio (DER) on the financial performance of automotive companies listed in IDX period 2015-2018. The population in this study was all Manufacturing Companies Listed on the Indonesia Stock Exchange Otomotive Sector as many as 9 companies and a sample of 9 companies with 4 years of observation amounted to 36 samples. The data collection techniques used in this study are documentation. The results showed that debt to asset ratio (DAR) has partially no effect on the Financial Performance of Automotive Companies Listed on the Indonesia Stock Exchange, Debt to Equity Ratio (DER) partially affects the Financial Performance of Automotive Companies Listed on the Indonesia Stock Exchange and Debt to Asset Ratio (DAR) and Debt to Equity Ratio (DER) simultaneously have an effect and significance on the Financial Performance of Automotive Companies Listed on the Indonesia Stock Exchange with a value of R Square of 0.694 or 69.4% which means variations in financial performance are measured by return on equity (ROE) with debt to asset ratio (DAR) And debt to equity ratio (DER) while the remaining 30.6% of other variables not studied by this study , e.g. company size, liquidity of the company and other variables.